2016
DOI: 10.1108/pijpsm-01-2015-0012
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of dual arrest for offenders involved in heterosexual domestic violence arrests

Abstract: Purpose – The purpose of this paper is to investigate the impact of extra-legal and legal predictors on dual arrest outcome for men and women arrested for domestic violence. Design/methodology/approach – This study analyzed 4,163 heterosexual domestic violence incidents over a five-year period (2002-2006). Using bivariate analyses and gender-stratified logistic regression this study: identified the variables associated with dual arrest; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 38 publications
4
9
0
Order By: Relevance
“…Finally, alcohol involvement was the strongest correlate of arrest. This also reiterates previous research where alcohol consumption has been correlated with arrest (Dichter et al, 2011; Durfee & Fetzer, 2016; Eitle, 2005; Hamilton & Worthen, 2011; Melton, 2012; Roark, 2016). This study did not account for demeanor while intoxicated, alcohol consumption functioned as a proxy for demeanor and compliance with police.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Finally, alcohol involvement was the strongest correlate of arrest. This also reiterates previous research where alcohol consumption has been correlated with arrest (Dichter et al, 2011; Durfee & Fetzer, 2016; Eitle, 2005; Hamilton & Worthen, 2011; Melton, 2012; Roark, 2016). This study did not account for demeanor while intoxicated, alcohol consumption functioned as a proxy for demeanor and compliance with police.…”
Section: Discussionsupporting
confidence: 89%
“…The most robust and consistent predictors of arrest in IPV incidents included the presence of a weapon (Dichter et al, 2011; Durfee & Fetzer, 2016; Eigenberg et al, 1996; Eitle, 2005; Hamilton & Worthen, 2011), victim injury (Bachman & Coker, 1995; Buzawa & Austin, 1993; Dichter et al, 2011; Durfee & Fetzer, 2016; Eitle, 2005; Hamilton & Worthen, 2011; Robinson & Chandek, 2000; Tatum & Pence, 2015), presence of witnesses (Buzawa & Austin, 1993; Eigenberg et al, 1996; Hamilton & Worthen, 2011; Robinson & Chandek, 2000), and victim preference (Buzawa & Austin, 1993; Eigenberg et al, 1996). Extralegal factors, such as alcohol involvement, have also predicted arrest (Dichter et al, 2011; Durfee & Fetzer, 2016; Hamilton & Worthen, 2011; Roark, 2016). In terms of race/ethnicity, some studies have demonstrated that arrest has increased in IPV incidents involving White victims when compared with other racial/ethnic groups (Dichter et al, 2011; Eitle, 2005; Hamilton & Worthen, 2011; McCormack & Hirschel, 2018).…”
Section: Police Response To Ipv and Stalkingmentioning
confidence: 99%
“…Some studies have looked at the factors that are present in dual arrest cases. Studies have identified that DFV incidents that involve alcohol or drugs are more likely to result in dual arrest (Muftic, Bouffard and Bouffard 2007;Roark 2016), with one study finding that women's odds of dual arrest increased when her male partner alone was under the influence of drugs or alcohol (Roark 2016). Limited attention has been paid to the potential consequences of criminalisation through the hybrid DVO system in the Australian context.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that perpetrators are often intoxicated during the commission of domestic violence (Leonard & Quigley, 1999; O’Brien et al, 2016; Thompson & Kingree, 2006) and that perpetrators of domestic violence are more likely to be arrested if intoxicated (Feder, 1997; Jones & Belknap, 1999). This relationship holds for arrested women and dual arrests (Fraehlich & Ursel, 2014; Houry, Reddy, & Parramore, 2006; Martin, 1997; Roark, 2016). Further complicating the dynamics is that victims, too, may use substances as a coping strategy (Anderson, 2002; Dutton et al, 2006; Logan, Walker, Cole, & Leukefeld, 2002; O’Brien et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Jones and Belknap (1999) found in their sample that 65.6% of victims initiated police contact (compared with 2.6% of children and 5.8% of offenders) but that victim-initiated contact with the police did not increase the likelihood of police action (i.e., jail, warrant, book and release, or court summons). Whereas, when a domestic violence arrest has been made, Roark (2016) discovered that who contacted the police impacted the dual arrest outcome. Of special importance to the current study is not only who contacted the police but also the role of the child.…”
Section: Introductionmentioning
confidence: 99%